Fidelity-Aware Multipath Routing for Multipartite State Distribution in Quantum Networks - Evan Sutcliffe; Alejandra Beghelli (IEEE Transactions on Quantum Engineering, 2025)
We consider the problem of distributing entangled multipartite states across a quantum network with improved distribution rate and fidelity. For this, we propose fidelity-aware multipath routing protocols, assess their performance in terms of the rate and fidelity of the distributed Greenberger–Horne–Zeilinger (GHZ) states, and compare such performance against that of single-path routing. Simulation results show that the proposed multipath routing protocols select routes that require more Bell states compared to single-path routing, but also require fewer rounds of Bell state generation. We also optimized the tradeoff between distribution rate and fidelity by selecting an appropriate cutoff to the quantum memory storage time. Using such a cutoff technique, the proposed multipath protocols can achieve up to an 8.3 times higher distribution rate and up to a 28% improvement in GHZ state fidelity compared to single-path routing. These results show that multipath routing both improves the distribution rates and enhances fidelity for multipartite state distribution.